'Open' or 'Closed'? Participation in English Manorial Presentment Juries, c.1310–c.1600: A Quantitative Approach. (30th August 2022) - Gibbs, Spike
Abstract: Historians of both the medieval and early modern eras have characterised the governing structures of rural communities as being dominated by local elites. However, interpretations are hampered by a lack of clear criteria against which to evaluate whether a village-governance regime was 'open, ' and characterised by wide participation, or 'closed', and characterised by the narrow restriction of office to an elite group, making it difficult to draw comparisons across time and space. This article uses a set of quantitative methodologies to solve this problem. It examines presentment juries in the manorial court, a governing institution which straddles the late medieval and early modern period, in three case-study communities for the period from 1310 to 1600. By applying four measures of participation, the article reveals that post-Black Death juries were characterised by a nuanced system of restriction. They were open in the sense that a large proportion of the male population, drawn from a wide range of families, acted as jurors and there was a continuous turnover in jury panels. However, they were also closed in that a small group of prominent individuals and families served a disproportionately frequent number of times. The results also question an established narrative of increasing monopolisation of village governance by a new 'middling sort' over the sixteenth century. Instead, change over time and space reveals a variable set of trends, with no universal linear pattern. The inflexibility of manorial institutions, combined with local demographic regimes and trends in landholding, led to significant differences in political participation between communities.